REVISION OF THE PURPURICENUS INTERSCAPILLATUS SPECIES - GROUP AND ALLIED TAXA (Coleoptera, Cerambycidae) - Rapuzzi, Pierpaolo; Sama, Gianfranco (Fragmenta entomologica, 2013)
A systematic study on Purpuricenus interscapillatus Plavilstshikov, 1937 and related species from southern European and Near East areas is here presented. Several changes in rank status and a new synonymy are proposed, and four new subspecies are described as below: Purpuricenus interscapillatus ssp. barbarae n. ssp. (NW Israel); Purpuricenus interscapillatus ssp. hermonensis n. ssp. (NE Israel); Purpuricenus renyvonae ssp. neocaucasicus n. ssp. (Turkey, Caucasus); Purpuricenus globulicollis ssp. skypetarum n. ssp. (Albania). The following nomenclatural changes are also introduced: Purpuricenus interscapillatus ssp. nabataeus Sama, 1999 stat. nov.; Purpuricenus interscapillatus ssp. cornifrons Pesarini & Sabbadini, 1992 stat. nov.; Purpuricenus interscapillatus ssp. longevittatus Pic, 1941 stat. nov.; Purpuricenus apiceniger Pic, 1914 stat. nov. After studying of the type specimen the following new synonymy is also proposed: Purpuricenus kaehleri ssp. menetriesi Motschulsky, 1845 = Purpuricenus budensis var. caucasicus Pic, 1902 syn. n.